Meningkatkan Hasil Belajar Siswa dan Penguasaan Materi Persamaan Linear Dua Variabel Melalui Soal Cerita Bagi Siswa Kelas X SMAN 2 Lengayang Semester 2 Tahun 2020/ 2021 - Titin Anggraini (Journal on Education, 2023)
This research was conducted with the aim of improving student learning outcomes and mastery of linear equation material through independent practice for class X students of SMAN 2 Lengayang. This research is class action research (CAR). The subjects in this study were 30 students in class X SMA Negeri 1. This research was carried out from July to September 2021 in the 2020/2021 Learning Year in Class X IPA 2 SMAN 2 Lengayang. This research was conducted in two cycles. Where each cycle begins with planning, implementation, observation/reflection and follow-up. Based on the results of the research, it was concluded that through independent practice it can improve student learning outcomes in mastering linear equation material, namely class X A teachers. The classroom action research procedure used refers to the action research methodology, namely (1) planning, (2) implementation action, (3) observation and evaluation, (4) reflection, which was carried out in 2 cycles. Independent practice is a question exercise in which students create questions and their solutions after receiving the material and are accompanied by examples and how to solve them. The results of the independent exercise in cycle 1 showed that the skills of students in making questions and their solutions were 84.62%, and the results of the exercises in cycle 2 of students' skills reached 92.86%. Meanwhile, the average test result for cycle 1 was 71.9 and the average test result for cycle 2 was 79.9. This shows an increase in student learning outcomes. In this class action research, it can be concluded that independent practice can improve mastery of linear equation material for class X students of SMAN 2 Lengayang semester 2 of 2020/2021.